2019
DOI: 10.3390/agronomy9030139
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Growth Response of Pepper (Capsicum annum L.) Seedlings to Supplementary Red/Blue Light Revealed through Transcriptomic Analysis

Abstract: Red and blue light have great effects on physiological processes and growth of plants. In this experiment, we investigated the physiological and growth response of pepper (Capsicum annuum L.) to supplementary red:blue (4:1) light for 1 h (T1), 3 h (T2), and 5 h (T3), and the full-spectrum light-emitting diodes, LEDs, as control (CK). Thirty-day-old seedlings were grown under these treatments for 20 days in a climate-controlled room before data measurement. The results showed that the light treatments significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 41 publications
1
26
0
Order By: Relevance
“…Biomass is an important indicator of seedling quality. In this study, the seedling DW under RB was signi cantly greater than those under other treatments, which suggested that this spectrum was optimal because it promoted plant development and drove photosynthesis by increasing Chl a and total Chl contents in the seedlings [33,40]. Previous studies also found that mixed R and B light could promote fresh weight (FW) and DW in many other plant species, such as chrysanthemum, upland cotton and tomato [41][42][43].…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Biomass is an important indicator of seedling quality. In this study, the seedling DW under RB was signi cantly greater than those under other treatments, which suggested that this spectrum was optimal because it promoted plant development and drove photosynthesis by increasing Chl a and total Chl contents in the seedlings [33,40]. Previous studies also found that mixed R and B light could promote fresh weight (FW) and DW in many other plant species, such as chrysanthemum, upland cotton and tomato [41][42][43].…”
Section: Discussionmentioning
confidence: 66%
“…The popularity of sweet pepper (Capsicum annuum L.) for fresh market consumption or in ready-to-eat food has risen signi cantly during the past decades and these peppers are mostly produced in protected environments [31]. Mixed R and B light has an apparent in uence on the growth and physiology of pepper plants [26,32,33]. Gaining a more complete mechanistic picture of how plants adapt and respond to R and B light quality is important since light quality plays important roles in growth and physiology.…”
mentioning
confidence: 99%
“…Therefore, more attention was given in recent years to physical factors that may be applicable to processing of sowing material [1,2]. In order to ensure a high seed performance, various methods of processing are used, including chemical preparations, such as seed inoculation by chemical material and growth regulators, as well as physical factors, including laser light and magnetic fields [3][4][5][6][7][8]. Pre-sowing treatment was applied in order to stimulate the seeds to better germinate and grow faster in various sowing conditions [9].…”
Section: Introductionmentioning
confidence: 99%
“…Research on the effects of pre-sowing bio-stimulation on plant crops showed that the best results of this treatment are obtained for plant vegetables, rather than for cereals and root crops. After applying radiation laser to tomatoes and cucumbers, a significant increase in yield was found, which accelerated the ripening and produced better fruit quality [8,22]. One of the methods of seed refinement is irradiation; a divergent beam laser light provides energy to modify physiological and biochemical processes, causing an increase in the field's performance to rise and yield crops [23].…”
Section: Introductionmentioning
confidence: 99%
“…The popularity of sweet pepper (Capsicum annuum L.) for fresh market consumption or in ready-to-eat food has risen significantly during the past decades and these peppers are mostly produced in protected environments [31]. Mixed R and B light has an apparent influence on the growth and physiology of pepper plants [26,32,33]. Gaining a more complete mechanistic picture of how plants adapt and respond to R and B light quality is important since light quality plays important roles in growth and physiology.…”
Section: Introductionmentioning
confidence: 99%